Spatiotemporal database models and languages for moving objects: A review - Silva, Joaquim P. (2010)
Geographic Information Systems and mobile devices, using wireless technology or the Global Position System, have proliferated in the last decade and made available huge amounts of spatial data. Applications of spatial data are spreading and new purposes are expected. The extensive use of mobility data is among the most promising applications. However, database models and technology to fully explore the potential of mobility data are lacking. This paper presents a short overview of the significant research in the spatiotemporal data models and query languages fields, and summarizes some of the research open issues.